COVID-19 and the taxation of professional athletes` image rights - Carrick, S. (The International Sports Law Journal, 2020)
The COVID-19 pandemic has raised and will continue to raise issues for sport for some time to come. In particular, the pressure put on athletes by politicians to take wage deductions and wage deferrals has caused controversy. This scrutiny of athletes` tax affairs is not unusual, given the particular and somewhat constant media focus, coupled with HMRC`s `Football Compliance Project` regarding footballer`s use of image rights companies to make tax deductions. This focus often presents footballers in an unflattering light. However, the purpose of this article is to demonstrate that the issues regarding athlete image rights are generally not due to overly sophisticated or overt actions by footballers and/or their agents but are the consequence of a convoluted system of taxation. Ultimately, HMRC guidance allows athletes to exploit an `image right` to make tax savings. This `image right` does not exist in law. Thus, this article will show that the current controversy surrounding footballers and their tax affairs is not a novel concept and that in the context of image rights athletes, clubs and agents have been forced to navigate a system of tax which is confusing, at best. In short, the issues surrounding footballers and image rights are due to the fact that `image rights` are protected in one area of law yet do not exist in another.